The role of federalism in European integration in the context of contemporary multifaceted challenges - Tzagkarakis, Stylianos Ioannis (Advances in Social Sciences Research Journal, 2021)
Federalism is a theory which has largely affected the European integration process and it remains important today. From the financial crisis and the requests for the creation either of Eurobonds or of a unified banking sector, to the current health crisis and the request for a common health policy approach and a common recovery mechanism for the elimination of the negative economic and social consequences of the pandemic, the theoretical and empirical discussion about the direction that European integration should follow are yet active. In this essay we will firstly outline some basic aspects of the theory of federalism as well as a brief comparison with other theories and secondly, we conduct an analysis on the contemporary importance of federalism. Accordingly, an evaluation of the theory with real examples-challenges offers lucrative ground in order to reach some tentative conclusions on the current and future role of federalism to the European integration process.